1998
DOI: 10.1086/311122
|View full text |Cite
|
Sign up to set email alerts
|

A Starburst Revealed—Luminous Radio Supernovae in the Nuclei of Arp 220

Abstract: We report 18 cm VLBI continuum imaging observations of Arp 220, the prototype luminous infrared galaxy (log). In previous work, we showed that Arp 220 has compact, high-nuclear radio emission L ϭ 12.11 L T fir , b that might be interpreted as a dust-enshrouded active galactic nucleus (AGN) radio core, or, alternately, as multiple, very luminous radio supernovae from a very active nuclear starburst. In this work, we present a new 18 cm VLBI image, with mas angular resolution, showing approximately a dozen unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
231
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(251 citation statements)
references
References 15 publications
20
231
0
Order By: Relevance
“…Sa8 indicates that the luminosity from the Arp 220 western nucleus could be generated by 200−1000 super-star clusters. An important contribution from star formation to the luminosity of the western nucleus is indeed evident (e.g., Smith et al 1998;Lonsdale et al 2006), and the apparent lack of strong X-ray emission from X-ray binaries associated with star formation (Lonsdale et al 2006) can be interpreted in terms of extreme absorption column densities (Sa08, this work).…”
Section: Sources Of Luminositymentioning
confidence: 93%
“…Sa8 indicates that the luminosity from the Arp 220 western nucleus could be generated by 200−1000 super-star clusters. An important contribution from star formation to the luminosity of the western nucleus is indeed evident (e.g., Smith et al 1998;Lonsdale et al 2006), and the apparent lack of strong X-ray emission from X-ray binaries associated with star formation (Lonsdale et al 2006) can be interpreted in terms of extreme absorption column densities (Sa08, this work).…”
Section: Sources Of Luminositymentioning
confidence: 93%
“…At the same time, Smith et al (1998) resolved the radio nucleus of Arp 220 and found many radio-emitting point sources, which were identified as SNRs. They estimated the SFR in Arp 220 as about 50-100 M yr −1 and estimated he supernova rate in the galaxy as 1.75-3.5 yr −1 .…”
Section: Supernovae In Starburst Regionsmentioning
confidence: 97%
“…Examples of these have been imaged at higher resolution by the Very Long Baseline Array (VLBA), in Arp 220 (Smith et al 1998) and Mrk 231 (Taylor et al 1999). The total radio powers can be used to estimate the associated supernova rates that would be required to account for the radio sources.…”
Section: No 2 2002 Agns In H II Galaxiesmentioning
confidence: 99%